Tata Kelola Badan Usaha Milik Desa "Mutiara Welirang" dalam Meningkatkan Daya Saing Desa Wisata Berbasis Good Governance di Desa Ketapanrame - Senaen, Windriyani Maharani; Trianggraini, Sela Ajeng; Lubis, Lunariana; Musleh, Moh. (Kolaborasi : Jurnal Administrasi Publik, 2024)
This research aims to analyze the application of good governance principles in the management of the Village-Owned Enterprise (BUMDes) "Mutiara Welirang" in Ketapanrame Village, which focuses on improving the competitiveness of the tourism village. This research uses a qualitative approach with a case study to understand how principles such as consensus, participation, accountability, transparency, and sustainability are applied in the management of the BUMDes. The results show that most of the principles of good governance are well implemented, especially in the aspects of community participation and decision-making through village deliberation. However, challenges still exist in the aspects of transparency and accountability, especially in terms of the accessibility of financial information for the community. In addition, limited human resources in management and funds for infrastructure development are major constraints in improving the competitiveness of tourism villages. This research suggests that BUMDes should improve the capacity of managers through managerial training, strengthen transparency, and seek alternative funding sources to support the development of tourism village infrastructure. Optimal implementation of good governance principles can assist BUMDes in creating sustainable, efficient and competitive tourism villages in the future.